Effect of dietary modification on the frequency of vasomotor symptoms in the menopausal women - زيدو كارمن; مروان عيسى (Latakia University Journal -Medical Sciences Series, 2024)
Women go through menopause, which begins after the age of 45 years. It is characterized by the cessation of the menstrual cycle because of a decrease in the secretion of female hormones; It is accompanied by many symptoms such as hot flashes, night sweats, sleep and mood disorders, back and joint pain, and chronic fatigue. Hot flashes are considered one of the most important symptoms during this stage. Low estrogen is the main cause of it, and there are many treatment methods for hot flashes, such as hormonal therapy with estrogen and progesterone, which is considered the most effective option, but it may cause some complications and side effects, so women began to search for safe treatment alternatives, and lifestyle modification by following A healthy diet is an effective method. This study aimed to evaluate the effect of diet modification on the frequency of hot flashes and night sweats. The results of the study showed a significant decrease in the frequency of vasomotor symptoms in women in the experimental group to whom the diet modification was applied after three months compared to women to whom this modification was not applied in the control group, the study recommended adopting dietary modification in women who suffer from vasomotor symptoms and conducting further studies on this subject on larger samples of women and longer follow-up periods.